The Relationship Of Nutrition Conscious Family Application With The Nutritional Status Of Toddlers At Lotu Puskesmas, Lotu District, Nias Utara Regency In 2019 - Lely Desi Uli Basana; Dedi Mizwar Tarihoran (Science Midwifery, 2019)
One of the specific nutrition interventions and efforts to overcome nutritional problems is by applying the behavior of Kadarzi (nutrition conscious family). Kadarzi is a program that has been implemented in Indonesia since 2007 until now. Based on nutrition development activities in North Sumatra in 2015, several indicators of Kadarzi were obtained, namely toddlers weighed 74.2% and a target of 80%, exclusive breastfeeding 57% of the 80% target, the use of iodized salt by 79.6% of the 90% target and the provision of nutritional supplements by 90.5% from the target of 90%. The type of research used is a quantitative study with a cross sectional research design, the sampling technique used is total sampling. The population in this study were all toddlers aged 6-59 months in the work area of the Lotu Health Center in 2019 as many as 147 toddlers. The study was conducted to determine the relationship between the application of nutrition-aware families and nutritional status. The results showed that the level of application of nutritionally aware families was good, there were 138 (94.2%) toddlers whose nutritional status was normal, from 9 respondents whose level of application of nutritionally aware families was less, there were 3 (2.1%) toddlers whose nutritional status was normal, and 6 toddlers whose nutritional status is not good. Based on statistical tests using the Chi Square test, the results showed that there was a significant relationship between the application of nutrition-aware families and the nutritional status of children under five with a p-value (0.001).